PRELIMINARY STUDY ON GAMMA-RAY CARGO SCANNER DESIGN FOR INDONESIAN PORTS - Ismet Isnaini; Nawa Yunia Ekariyani; Sapta Teguh Prasaja; Fitri Suryaningsih (BATAN, 2021)
Cargo scanning has become a popular method of preventing illicit goods from entering a particular country. The manual inspection system would consume time and cost; therefore, a non-intrusive inspection is desirable. The use of x-ray has replaced the manual system in many places, however, due to its nature of penetration, it cannot describe the content of the cargo precisely. The use of gamma-ray would increase the resolution image produces, hence verifying the content of the cargo as stated in the documents. Indonesia which has about 636 seaports has a high need for such system since smuggling of goods and human trafficking is very common in the country. Few existing gamma-ray cargo scanning systems have been installed in several ports in Indonesia, however, it is still imported and costs a fortune. The Nuclear Energy Agency of Indonesia initiates the development of such system with the increase of local content starting from its design until the manufacturing. This study will show the existing system and try to propose some mechanical and electrical user requirements for the system. The use of local content should become the primary consideration in the design to reduce the cost of the development. Keywords: Gamma Ray, Cargo Inspection, Security